Allergen-Specific Immunotherapy for Food Allergy: Latest Advances in Vaccines - Docena, Guillermo Horacio (2016)
Allergic diseases pose a global and growing health concern which has increased worldwide in the last years. Allergy results from a complex interaction between environmental factors and genes. In light of the increase in prevalence and costs of food allergy, both in developed and developing countries, effective methods of prevention and treatment would be clinically desirable since food is an integral part of life, but in some cases it can also be deadly for many people.